2010
DOI: 10.1088/0953-2048/24/1/015006
|View full text |Cite
|
Sign up to set email alerts
|

Resistive transition in disordered superconductors with varying intergrain coupling

Abstract: The effect of disorder is investigated in granular superconductive materials with strong and weak links. The transition is controlled by the interplay of the tunneling g and intragrain g intr conductances, which depend on the strength of the intergrain coupling. For g ≪ g intr , the transition involves first the grain boundary, while for g ∼ g intr the transition occurs into the whole grain. The different intergrain coupling is considered by modelling the superconducting material as a disordered network of Jos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…We speculate that the field‐induced shrinking of the size of superconducting domains may trigger size effects at a certain point. This possibly explains the sudden onset of the foot feature for V g > 2 V. It is notable that the foot feature also resembles the effects seen in previous work, in which reduced dimensions of the superconducting materials resulted in a similar trend below T c . Ponta et al have suggested that a resistive transition is possible to model by varying the inter‐grain coupling , while others have demonstrated size modulation and proximity effect on such coupling .…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…We speculate that the field‐induced shrinking of the size of superconducting domains may trigger size effects at a certain point. This possibly explains the sudden onset of the foot feature for V g > 2 V. It is notable that the foot feature also resembles the effects seen in previous work, in which reduced dimensions of the superconducting materials resulted in a similar trend below T c . Ponta et al have suggested that a resistive transition is possible to model by varying the inter‐grain coupling , while others have demonstrated size modulation and proximity effect on such coupling .…”
Section: Resultssupporting
confidence: 77%
“…Severe hole depletion from the grain boundaries may lead to an interfacial insulating state such that the conductivity across the grain boundaries may be explained via variable range hopping, where the electron–electron interaction differs as compared to that where enough free carriers are available (such as deep within the grains) . Also, by electrostatically modifying the film, we enter into a regime where Coulomb interaction effects and mesoscopic fluctuations are no longer negligible . Therefore, we expect that the charges driven by the source–drain voltage into a grain boundary from the grains experience strong scattering.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the macroscopic superconductivity is established progressively through the Josephson proximity coupling effect among the locally disconnected superconducting grains possessing dimensional dependent distribution of critical temperature. We emphasize that disorder induced inhomogeneity 19 , finite size effect (FSE) for quasi zero-dimensional (0D) grains and the phase fluctuation are the main reasons behind the wide transition and resistive tailing. Besides, the appearance of PSLs in the IVC s and their evolution with film thickness indicate that disordered superconducting Nb 2 N can be of future interests in the field of PS based studies and applications.…”
Section: Introductionmentioning
confidence: 99%
“…In order to address such investigation, the paper presents an agent-based model and simulation based on empirical data collected by questionnaires. Simulation is a useful tool to investigate complex systems in many different fields such as engineering, physics, mathematics, and economics and is also becoming an increasingly significant methodological approach in organizations and strategy and public management field [11][12][13][14][15][16]. Among the different simulation models, the agent-based approach is very useful to investigate complex systems and networks characterized by a large number of simple interacting units [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%